Developing Augmented Reality-Based Learning Media in Improving Young Learnersâ€™ Short Story Listening Skills - Yatri, Nadya Dewi; Sismulyasih, Nugraheti (Universitas Pendidikan Mandalika, 2024)
The lack of innovation and variety of media used in the Indonesian language learning process causes a lack of listenin skills for students short stories. This research is shown to create a learning media product in the form of a short story book based on augmented reality which can be effectively used to improve students listening skills. The type of research used is research and development with reference to the ADDIE model with the stages of analyze, design, development, implementation, and evaluation. Subjects for small scale trials of this study used 6 students and on a large scale trial using 31 students. The product validation test was carried out by 1 media expert and 1 material expert. Data collection methods used observation, interviews, and questionnaires. The product effectiveness test used t-test and N-Gain test. The results explain that augmented reality-based storybook learning media is said to be feasible with 91% value achievement from media experts and 89% support from material experts. These results also provide an effectiveness value through the t-test analysis test value Ha is accepted and the N-Gain obtained is Â³ 0.70. Thus it can be explained simply that the learning media is feasible and effective to use in learning Indonesian, especially in short story listening skills. The development of this media can be used by teachers to support interesting and fun learning so that it can improve listening skills.